Nominata of the Reviewers of the volume 3, 2013 - Maria Claudia Nogueira Zerbini; Fernando Peixoto Ferraz de Campos; Aloisio Felipe-Silva; Maria Alice de França Rangel Rebello (University of São Paulo, 2013)
The Editors of Autopsy and Case Reports thank the peer reviewers listed below for the excellent collaborative work, opinions and comments on the papers published in 2013. Their hard work certainly contributed to maintaining the scientific level of this journal.